2018
DOI: 10.1103/physreva.98.043412
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced atomic desorption of lithium

Abstract: We demonstrate loading of a Li magneto-optical trap using light-induced atomic desorption. The magnetooptical trap confines up to approximately 4 × 104 7Li atoms with loading rates up to approximately 4 × 103 atoms per second. We study the Li desorption rate as a function of the desorption wavelength and power. The extracted wavelength threshold for desorption of Li from fused silica is approximately 470 nm. In addition to desorption of lithium, we observe light-induced desorption of background gas molecules. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…However, UV light also desorbs other, unwanted species from surfaces, such as water and oxygen [49, 50, 51], increasing their background gas pressures. In a recent experiment [48], we observed that the increase in pressure due to unwanted gasses is significantly smaller than our low-outgasssing lithium dispensor. In addition, light-assisted desorption should be nearly instantaneous with application of the light, eliminating the need for a mechanical shutter.…”
Section: Details Of the Planned Devicementioning
confidence: 49%
See 1 more Smart Citation
“…However, UV light also desorbs other, unwanted species from surfaces, such as water and oxygen [49, 50, 51], increasing their background gas pressures. In a recent experiment [48], we observed that the increase in pressure due to unwanted gasses is significantly smaller than our low-outgasssing lithium dispensor. In addition, light-assisted desorption should be nearly instantaneous with application of the light, eliminating the need for a mechanical shutter.…”
Section: Details Of the Planned Devicementioning
confidence: 49%
“…We are also considering other more speculative sources of lithium. Lithium, like other alkali-metal atoms, can be desorbed from surfaces using UV light [48]. However, UV light also desorbs other, unwanted species from surfaces, such as water and oxygen [49, 50, 51], increasing their background gas pressures.…”
Section: Details Of the Planned Devicementioning
confidence: 99%
“…Our design can easily be adapted to serve as cold gas source for a variety of applications. By implementing differential pumping or using a low-outgassing atom source (rather than a dispenser) [46,47], our device could be used as a primary vacuum gauge [9,10]. The diffraction grating period and etch depth can be altered to optimize trapping of other elements, such as Rb, Cs, Ca, Sr, or Yb.…”
Section: Discussionmentioning
confidence: 99%
“…To produce a gated cloud of atoms one can employ the light-induced atomic-desorption (LIAD) process. In the LIAD process, also known as the photo-electric effect for atoms, high energy laser pulses hit the wall of an atomic vapor cell, which is coated with alkali atoms and desorb them from the surface [38][39][40][41] . The inset of Fig.…”
Section: Atom-light Interactions and Monte-carlo Simulationsmentioning
confidence: 99%